Comparison of oral midazolam with oral tramadol, triclofos and zolpidem in the sedation of pediatric dental patients: An in vivo study - S Bhatnagar; U M Das; G Bhatnagar (Wolters Kluwer Medknow Publications, 2012)
Objective: oral sedation is the simplest and most convenient sedation method for managing uncooperative child patients because it is easy to administer and there is no need for nasal hood or injection. Oral midazolam is the most commonly used preanesthetic medication for children. When given in amounts between 0.5 and 0.75 mg/kg of body weight, oral midazolam has been found to be an effective sedative agent for pediatric outpatients. Tramadol is a synthetic, centrally acting analgesic indicated for moderate to severe pain. Chloral hydrate is one of the sedatives most commonly used, has excellent absorption, fast induction, and exert minimal effects on respiration. zolpidem is the most commonly prescribed hypnotic due to its clinical efficacy, safety, and ability to be well tolerated with patients. Materials and Methods: 60 anxious and fearful children who reported to the department were treated under conscious sedation for the accomplishment of dental treatment. Patients were randomly assigned to four groups. Statistical analysis was done using Kruskal Wallis Test and decision criterion was to reject the null hypothesis if the P-value is less than 0.05. Results: it was observed that there is a statistically significant difference in median scores recorded for the level of sedation between the different groups (P < 0.001). Conclusion: this study concluded that midazolam is the best drug for producing conscious sedation followed by tramadol and triclofos. Zolpidem was not able to produce a sufficient level of sedation and it cannot be supported as a sedative agent at the present dosage.